The Wolverine [videorecording (DVD)] - Jackman, Hugh; Lee, Will Yun, 1971-; Okamoto, Tao (20th Century Fox, 2013)
Summoned to Japan by an old acquaintance, Wolverine becomes embroiled in a conflict that forces him to confront his own demons.